Friedrich Nietzsche y las conferencias de Basilea sobre la historia de la literatura griega (2018)
The lectures held by Friedrich Nietzsche when he had the professorship of Greek Language and Literature between 1869 and 1879 at the University of Basel, are today the least known of the philosopher´s Nachlass. These writings allow for a reconstruction of the relationship of the philosopher with the Greek world in all its complexity and in an alternative way to that which arises from the Birth of Tragedy. The aesthetic experience of the Greek world is an extremely complex phenomenon which is irremediably extraneous to the modern experience. It can been easily understood when we try to refer it to the framework of modern aesthetics. The incongruity which lies at the base is the conception itself of what we can refer to as culture in the modern society and in the ancient one: reading and writing and the consequent way and tools used for the transmission of knowledge.What can we learn from the ancient people? In order to answer this question Nietzsche investigates the birth process of a work of art in the Greek language. The analysis of the rigid norms which are characteristic of the literary genres will show an anti-romantic image of a strongly formal and conventional art, that is closely linked to complex norms connected to Public Institutions. A path of reﬂections on ethic and aesthetic concepts on shape and norm, discipline and convention in contrast to the opinions of an “irrationalist” Nietzsche shows itself in the lectures.  It will then be developed starting from Menschliches, Allzumenschliches to the entire Nietzsche production.